SPECIAL FEATURES OF LEGAL PROTECTION OF TRADE MARKS IN UKRAINE - Білоусов, Віталій Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article an author considers the concepts and features of trade mark by researching the effective legislation norms and the doctrinal points of view of academic lawyers. Methods of research: the mechanism of regulation of the rights to trade marks is analyzed and defined. Results: an author points his attention to disadvantages, discrepancies and conflicts in the legal regulation of trade marks. Recommendations for their elimination and amendments to the effective legislation are proposed. Discussion: the problems of domestic legislation on the protection of the rights to trade marks are discussed.